Melancholic Migrations and Affective Objects in Fadia Faqir’s My Name is Salma - Sibyl Adam (C21 Literature: Journal of 21st-century Writings, 2017)
Melancholia has been read as an individual pathological response to loss, a national cultural reaction to the end of the British Empire, and as a collective political emotion felt by socially marginalised groups. Fadia Faqir’s 'My Name is Salma' (2007) conceives of melancholia as exceeding both individual and national boundaries. The novel illustrates how processes of migrant melancholia are caught up with the gendered, religious and racial relationship of bodies, space and objects. Attempts to alleviate melancholia through investing in objects in line with normal cycles of mourning remain inconclusive due to the way consumerist spaces are structured to normalise whiteness. The novel’s engagement with melancholia as political through communal emotions that make visible injustice rejects Freudian notions of melancholia as negatively pathological. In particular, emotion has a didactic function by reminding the reader of structural inequalities and how the history of European imperialism fuels present-day xenophobia. Ultimately, by transforming prior understandings of melancholia, the novel shows how migrants are in a unique position to refute the national project that upholds designations of rights, citizenship and belonging.